2005
DOI: 10.1079/bjn20051512
|View full text |Cite
|
Sign up to set email alerts
|

Low amounts oftrans18 : 1 fatty acids elevate plasma triacylglycerols but not cholesterol and alter the cellular defence to oxidative stress in mice

Abstract: Trans fatty acids are found mainly in processed foods. It has been shown that when their intake is high, total cholesterol, LDL-cholesterol and triacylglycerols are elevated, while HDL-cholesterol decreases. To evaluate a possible effect of these compounds, even in low amounts, C57Bl/6J mice were fed for 7 weeks a diet containing 13·6 % energy as partially hydrogenated rapeseed oil-enriched diet (Trans diet). The Trans diet contained 3 % energy as trans 18 : 1 fatty acid (elaidic acid). Control mice were on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 39 publications
8
35
2
4
Order By: Relevance
“…Our laboratory's previous work has demonstrated that iTFAs dose-dependently initiate the atherogenic process (6). The source and dosage of TFA provided to the mice in this study [as well as our laboratory's previous work (6)] was similar in type and energetic load to previous clinical and experimental reports and to current human TFA consumption values (4,9,39). The diets providing elaidic acid rich, partially hydrogenated vegetable shortening in either a moderate (T) or high (HT) dose, provided 1.4 and 2.8% industrial source TFAs (iTFAs), representing 3.2 and 6.4% of caloric energy, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…Our laboratory's previous work has demonstrated that iTFAs dose-dependently initiate the atherogenic process (6). The source and dosage of TFA provided to the mice in this study [as well as our laboratory's previous work (6)] was similar in type and energetic load to previous clinical and experimental reports and to current human TFA consumption values (4,9,39). The diets providing elaidic acid rich, partially hydrogenated vegetable shortening in either a moderate (T) or high (HT) dose, provided 1.4 and 2.8% industrial source TFAs (iTFAs), representing 3.2 and 6.4% of caloric energy, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…Following ingestion, EA is typically integrated in the plasma membrane of cells [9] . EA has also been shown to induce oxidative stress, for example, an EA rich diet caused oxidative stress in mice due to EA-induced reduction in plasma vitamin E levels [10] . EA can also be incorporated into triglycerides, cholesterol esters, and phospholipids as well as other long-chain fatty acids, such as OA, linoleic acid, and palmitic acid [11] .…”
mentioning
confidence: 99%
“…It is also well known that TFAs can modify cellular functions by interacting with the hydrophobic regions of membrane proteins [34]. Furthermore, recent studies reported that TFAs might alter cell membrane permeability, eicosanoid production and gene expression [35][36][37]. Several interesting studies have reported on receptors for fatty acids.…”
Section: Discussionmentioning
confidence: 99%